THE KEY FEATURES OF TRANSLATION AND LOCALIZATION OF SCIENTIFIC AND TECHNICAL TEXTS - Ігнатюк, Ольга; Іонане, Надія (SWorldJournal, 2025)
This article explores the key aspects of translation and localization of scientific and technical texts. The increasing demand for high-quality technical translation arises from the rapid development of science and technology. Scientific and technical tex